Battery mixture, method for adjusting viscosity of battery mixture, method for producing battery mixture, method for producing battery member, battery member, secondary battery, and kit

CN122935833APending Publication Date: 2026-10-16KUREHA CORPORATION
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202580021344.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-28
Filing Date
2025-03-13
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

但是,用于分别制造固体电池的正极层、固体电解质层以及负极层的浆料存在若包含偏氟乙烯聚合物则可能发生凝胶化这一问题

Benefits of technology

[0063] According to the present invention, a battery compound capable of inhibiting gelation of a compound containing a vinylidene fluoride polymer is provided, as well as a method for preparing the viscosity of the battery compound, a method for manufacturing the battery compound, a method for manufacturing a battery component using the battery compound, a battery component and a secondary battery made from the battery compound, and a kit for manufacturing the battery compound are provided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to a battery mixture containing an oxime, a vinylidene fluoride polymer, and a solid electrolyte. Further, the present application relates to a viscosity adjustment method for a battery mixture, which has the following steps: a step of preparing a composition containing a vinylidene fluoride polymer, a solid electrolyte, and a nonaqueous solvent; and a step of adding an oxime to the composition. Further, the present application relates to a manufacturing method for a battery mixture, which has the following steps: a step of preparing an oxime, a vinylidene fluoride polymer, a solid electrolyte, and a nonaqueous solvent; and a step of mixing the oxime, the vinylidene fluoride polymer, the solid electrolyte, and the nonaqueous solvent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to battery additives, methods for adjusting the viscosity of battery additives, methods for manufacturing battery additives, methods for manufacturing battery components, battery components, secondary batteries, and kits. Background Technology

[0002] Solid-state batteries, which use solid electrolytes instead of liquid electrolytes, offer higher capacity and safety compared to liquid electrolyte batteries, and are therefore expected to be candidates for the next generation of rechargeable batteries.

[0003] Solid-state batteries are composed of a positive electrode layer, a solid electrolyte layer, and a negative electrode layer stacked together. Each layer contains a solid electrolyte and a binder. In the fabrication of the positive or negative electrode layer, a slurry-like mixture containing positive or negative active materials is further coated and dried, followed by a stamping process.

[0004] Vinylidene fluoride polymers are also used as binders for the various layers of solid-state batteries. However, there is a problem that the slurries used to manufacture the positive electrode layer, solid electrolyte layer, and negative electrode layer of a solid-state battery may gel if they contain vinylidene fluoride polymers. In response, Patent Documents 1 and 2 describe slurries using vinylidene fluoride polymers copolymerized with specific fluorinated monomers that retain fluidity even after tens of hours following manufacturing.

[0005] Existing technical documents

[0006] Patent documents

[0007] Patent Document 1: International Publication No. 2021 / 125150

[0008] Patent Document 2: International Publication No. 2022 / 054540 Summary of the Invention

[0009] The problem that the invention aims to solve

[0010] Patent Documents 1 and 2 describe that vinylidene fluoride polymers copolymerized from specific fluorinated monomers (e.g., trifluoroethylene) retain fluidity after manufacturing. However, according to the inventors' understanding, even slurries using their copolymers, when shear heating occurs in the slurry due to stirring during slurry preparation, while retaining fluidity, become very viscous, sometimes making coating difficult or causing gelation.

[0011] It should be noted that, regarding existing batteries using electrolytes, it is known that gelation may occur if the slurry used to manufacture the electrodes contains vinylidene fluoride polymers. However, as described in Patent Document 1, gelation of the slurry used in the manufacture of solid-state batteries is considered to occur due to the solid electrolyte used in the solid-state battery. Therefore, gelation of the slurry used to manufacture the electrodes of existing batteries cannot be equated with gelation of the slurry used to manufacture the layers of solid-state batteries. Methods for suppressing gelation of the slurry used to manufacture the electrodes of existing batteries may not be effective for the slurry used to manufacture the layers of solid-state batteries.

[0012] The present invention was made in view of the above circumstances, and its object is to provide a battery compound capable of suppressing gelation of a compound containing a vinylidene fluoride polymer, a method for preparing the viscosity of the battery compound, a method for manufacturing the battery compound, a method for manufacturing a battery component using the battery compound, a battery component and a secondary battery made from the battery compound, and a kit for manufacturing the battery compound.

[0013] Solution for solving the problem

[0014] One aspect of the present invention for solving the above problems relates to the battery compound described below [1] to [5].

[0015] [1] A battery compound comprising:

[0016] Oxime;

[0017] Polyethylene fluoride polymers; and

[0018] Solid electrolyte.

[0019] [2] According to the battery compound described in [1], wherein,

[0020] The ratio (η2 / η1) of the slurry viscosity (η2) after 3 hours from preparation to the slurry viscosity (η1) immediately after slurrying with the addition of non-aqueous solvents is less than 1.00.

[0021] [3] The battery compound according to [1] or [2], wherein,

[0022] The oxime content is as follows: the amount of hydroxyimino groups in the oxime is 6.0 mmol / g or more and 80.0 mmol / g or less relative to 1g of the vinylidene fluoride polymer.

[0023] [4] The battery compound according to any one of [1] to [3], wherein,

[0024] The oxime content is as follows: the amount of hydroxyimino groups in the oxime is more than 2.0 mmol / g and less than 70.0 mmol / g relative to 1g of the solid electrolyte.

[0025] [5] The battery compound according to any one of [1] to [4], wherein,

[0026] The vinylidene fluoride polymer contains more than 80 mol% of vinylidene fluoride-derived structural units relative to all structural units.

[0027] Another aspect of the present invention for solving the above problems relates to the viscosity adjustment method of the battery compound described in [6] to [7] below.

[0028] [6] A method for adjusting the viscosity of a battery compound, comprising the following steps:

[0029] A process for preparing a composition comprising a vinylidene fluoride polymer, a solid electrolyte, and a non-aqueous solvent; and

[0030] The step of adding oxime to the composition.

[0031] [7] According to the viscosity adjustment method of the battery compound described in [6], wherein,

[0032] The oxime is added to the gelled composition.

[0033] Another aspect of the present invention for solving the above problems relates to the viscosity adjustment method of the battery compound described below [8] to [9].

[0034] [8] A method for manufacturing a battery compound, comprising the following steps:

[0035] The process of preparing oximes, vinylidene fluoride polymers, solid electrolytes, and non-aqueous solvents; and

[0036] The process of mixing the oxime, the vinylidene fluoride polymer, the solid electrolyte, and the non-aqueous solvent.

[0037] [9] According to the method for manufacturing the battery compound described in [8], wherein,

[0038] The vinylidene fluoride contains 0.5 wt% or more of fluorinated compounds other than vinylidene fluoride.

[0039] Another aspect of the present invention for solving the above problems relates to a method for manufacturing a battery component as described below

[10] to

[12] .

[0040]

[10] A method for manufacturing a battery component, comprising the following steps:

[0041] The process of coating and drying a battery compound containing a non-aqueous solvent, according to any one of claims 1 to 5.

[0042]

[11] According to the manufacturing method of the battery component described in

[10] , wherein,

[0043] The battery compound contains electrode active materials.

[0044]

[12] The method for manufacturing the battery component according to

[10] or

[12] , wherein,

[0045] The battery compound does not contain electrode active materials.

[0046] Another aspect of the present invention for solving the above problems relates to the battery components described below

[13] and

[15] to

[17] .

[0047]

[13] A battery component manufactured by any one of

[10] to

[12] .

[0048]

[15] A battery component comprising:

[0049] Oxime;

[0050] Polyethylene fluoride polymers; and

[0051] Solid electrolyte.

[0052]

[16] According to the battery component described in

[13] , wherein,

[0053] The battery component contains electrode active materials.

[0054]

[17] The battery component according to

[15] or

[16] , wherein,

[0055] The battery component does not contain electrode active materials.

[0056] Another aspect of the present invention for solving the above problems relates to a secondary battery as described in

[14] and

[18] .

[0057]

[14] A secondary battery comprising the battery components according to

[13] .

[0058]

[18] A secondary battery comprising a battery component according to any one of

[15] to

[17] .

[0059] Another aspect of the present invention for solving the above problems relates to the kit described below

[19] .

[0060]

[19] A kit for manufacturing a battery compound according to any one of [1] to [5]

[0061] Oxime and other materials are stored in separate containers.

[0062] Invention Effects

[0063] According to the present invention, a battery compound capable of inhibiting gelation of a compound containing a vinylidene fluoride polymer is provided, as well as a method for preparing the viscosity of the battery compound, a method for manufacturing the battery compound, a method for manufacturing a battery component using the battery compound, a battery component and a secondary battery made from the battery compound, and a kit for manufacturing the battery compound are provided. Detailed Implementation

[0064] [mixture]

[0065] One embodiment of the present invention relates to a battery compound comprising an oxime, a vinylidene fluoride polymer, and a solid electrolyte.

[0066] Thickening and gelation of mixtures containing solid active substances also occur in mixtures used to form a solid electrolyte layer that does not contain positive or negative active substances. Therefore, it is believed that the thickening and gelation of the aforementioned mixtures are due to the solid active substances. In view of the inventors, by adding oxime to the thickening or gelling mixture, the viscosity of the mixture can be reduced, or by adding oxime during the preparation of the mixture, thickening and gelation of the mixture can be suppressed.

[0067] (oxime)

[0068] Oximes are compounds formed by replacing the oxygen atom of the carbonyl group of an aldehyde or ketone with a hydroxyimino group (=NOH). Oximes can be derived from either aldehydes (RCH=NOH) or ketones (R'RC=NOH).

[0069] There are no specific limitations on the types of oximes. Examples of oximes include: acetoxime, 2-butanone oxime (methyl ethyl ketone oxime), methyl isopropyl ketone oxime, methyl tert-butyl ketone oxime, di-tert-butyl ketone oxime, 2-pentanone oxime, 3-pentanone oxime, 1-cyclohexyl-1-propanone oxime, formaldehyde oxime, and acetaldehyde oxime. oxime), benzoyl oxime, benzaldehyde oxime, acetophenone oxime, benzophenone oxime, 4-hydroxyacetophenone oxime, cyclopropanone oxime, cyclobutanone oxime, cyclopentanone oxime, cyclohexanone oxime, cycloheptanone oxime, cyclooctanone oxime, cyclononanone oxime, cyclodecanone oxime, cyclododecanone oxime, benzoquinone dioxime, benzoquinone monooxime, 2,3-butanedione monooxime, Acetamide oxime, 3-hydroxy-3-methyl-2-butanone oxime, α-benzoin oxime, 1,3-dihydroxyacetone oxime, 2-isonitrosophenylacetone, dimethylglyoxime, methylethylglyoxime, diethylglyoxime, diphenylglyoxime, benzophenone dioxime, piperidone oxime, 2,4-pentanedione dioxime, 2-diethyl ether oxime, ethyl acetylhydroxamic acid, ethyl cyanoglyoxylate oxime, etc.

[0070] In addition, oximes can be polymers containing hydroxyimino groups (hereinafter also referred to as "oxime polymers") or oligomers containing hydroxyimino groups (hereinafter also referred to as "oxime oligomers").

[0071] Oxime polymers and oxime oligomers can be synthesized by polymerizing monomers or oligomers containing hydroxyimino groups, or by reacting hydroxylamines with polymers or oligomers having ketone groups in their backbone. Examples of polymers having ketone groups in their backbone include: poly(methyl vinyl ketone), polyketone (PK), polyether ketone (PEK), polyether ether ketone (PEEK), polyether ketone ketone (PEKK), polyether ether ketone ketone (PEEKK), and polyether ketone ether ketone ketone (PEKEKK), etc. Specific examples of oxime polymers and oxime oligomers include poly(methyl vinyl oxime), etc.

[0072] These oximes can be used in single or multiple ways.

[0073] These oximes can be represented by the oxime shown in equation (1) or the oxime shown in equation (2).

[0074] [Chemical Formula 1]

[0075]

[0076] In formula (1), R1 and R2 independently represent the following functional groups: hydrogen atom, aldehyde group, nitrile group, alkyl group with 1 or more but less than 10 carbon atoms, alkenyl group with 2 or more but less than 10 carbon atoms, alkynyl group with 2 or more but less than 10 carbon atoms, cycloalkyl group with 3 or more but less than 10 carbon atoms, cycloalkenyl group with 3 or more but less than 10 carbon atoms, aryl group with 6 or more but less than 18 carbon atoms, aralkyl group with 7 or more but less than 14 carbon atoms, or heterocyclic group with 3 or more but less than 13 carbon atoms. It should be noted that the above alkyl groups can be straight-chain, branched, or have ester bonds. R1 and R2 can also be bonded to each other to form a ring.

[0077] The alkyl group preferably has 1 or more and 10 or less carbon atoms, more preferably 1 or more and 5 or less, and even more preferably 1 or more and 2 or less. The alkenyl group preferably has 2 or more and 10 or less carbon atoms, more preferably 2 or more and 6 or less, and even more preferably 2 or more and 4 or less. The alkynyl group preferably has 2 or more and 10 or less carbon atoms, more preferably 2 or more and 6 or less, and even more preferably 2 or more and 4 or less. The cycloalkyl group preferably has 3 or more and 10 or less carbon atoms, more preferably 3 or more and 7 or less, and even more preferably 5 or more and 7 or less. The aryl group preferably has 6 or more and 18 or less carbon atoms, more preferably 6 or more and 10 or less, and even more preferably 6 or more and 8. The aralkyl group preferably has 7 or more and 14 or less carbon atoms, more preferably 7 or more and 11 or less, and even more preferably 7 or more and 9 or less. The heterocyclic group preferably has 3 or more and 13 or less carbon atoms, more preferably 3 or more and 10 or less, and even more preferably 3 or more and 8 or less.

[0078] [Chemical Formula 2]

[0079]

[0080] In formula (2), R3 and R4 independently represent the following functional groups: hydrogen atom, aldehyde group, nitrile group, alkyl group with 1 or more but less than 10 carbon atoms, alkenyl group with 2 or more but less than 10 carbon atoms, alkynyl group with 2 or more but less than 10 carbon atoms, cycloalkyl group with 3 or more but less than 10 carbon atoms, cycloalkenyl group with 3 or more but less than 10 carbon atoms, aryl group with 6 or more but less than 18 carbon atoms, aralkyl group with 7 or more but less than 14 carbon atoms, or heterocyclic group with 3 or more but less than 13 carbon atoms. It should be noted that the above alkyl groups can be straight-chain, branched, or have ester bonds. R3 and R4 can also bond to each other to form a ring.

[0081] The alkyl group preferably has 1 or more and 10 or less carbon atoms, more preferably 1 or more and 5 or less, and even more preferably 1 or more and 2 or less. The alkenyl group preferably has 2 or more and 10 or less carbon atoms, more preferably 2 or more and 6 or less, and even more preferably 2 or more and 4 or less. The alkynyl group preferably has 2 or more and 10 or less carbon atoms, more preferably 2 or more and 6 or less, and even more preferably 2 or more and 4 or less. The cycloalkyl group preferably has 3 or more and 10 or less carbon atoms, more preferably 3 or more and 7 or less, and even more preferably 5 or more and 7 or less. The aryl group preferably has 6 or more and 18 or less carbon atoms, more preferably 6 or more and 10 or less, and even more preferably 6 or more and 8. The aralkyl group preferably has 7 or more and 14 or less carbon atoms, more preferably 7 or more and 11 or less, and even more preferably 7 or more and 9 or less. The heterocyclic group preferably has 3 or more and 13 or less carbon atoms, more preferably 3 or more and 10 or less, and even more preferably 3 or more and 8 or less.

[0082] X represents a single bond or an alkylene group having 1 or more but less than 5 carbon atoms. The aforementioned alkylene groups can be straight-chain or branched.

[0083] From the viewpoint of effectively reducing the viscosity of thickening or gelling agents or effectively inhibiting the thickening and gelling of agents, the oxime shown in formula (1) is preferably an oxime in which R1 and R2 independently represent alkyl groups having 1 or more hydrogen atoms and 5 or fewer carbon atoms. The alkyl group can be straight-chain or branched. R1 and R2 can also be bonded to each other to form a ring. When the alkyl group constituting R1 or R2 is straight-chain or branched, the number of carbon atoms in one or both of the alkyl groups is preferably 1 or more and 3 or fewer, more preferably 1 or more and 2 or fewer, and even more preferably 1.

[0084] Furthermore, from the viewpoint of effectively reducing the viscosity of the thickening or gelling agent or effectively inhibiting the thickening and gelling of the agent, the total number of carbon atoms in R1 and R2 is preferably 1 or more and 3 or less, more preferably 1 or more and 2 or less, and even more preferably 1.

[0085] Furthermore, from the viewpoint of effectively reducing the viscosity of the thickening or gelling agent or effectively inhibiting the gelation of the agent, R1 and R2 are preferably bonded to each other to form a ring. The number of carbon atoms constituting the ring is preferably 3 or more and 12 or less, more preferably 4 or more and 8 or less.

[0086] More preferably.

[0087] Examples of oximes represented by formula (1) where R1 or R2 represents an alkyl group with 1 or more hydrogen atoms and less than 5 carbon atoms include: acetone oxime, 2-butanone oxime, methyl isopropyl ketone oxime, methyl tert-butyl ketone oxime, di-tert-butyl ketone oxime, 2-pentanone oxime, formaldehyde oxime, acetaldehyde oxime, butyraldehyde oxime, cycloacetone oxime, cyclobutanone oxime, cyclopentanone oxime, cyclohexanone oxime, cycloheptanone oxime, cyclooctanone oxime, cyclononanone oxime, and cyclodecanone oxime, etc.

[0088] Furthermore, from the viewpoint of effectively reducing the viscosity of thickening or gelling agents or effectively inhibiting the thickening and gelling of agents, the oxime shown in formula (2) is preferably an oxime in which R3 and R4 independently represent alkyl groups having 1 or more hydrogen atoms and 5 or fewer carbon atoms. The alkyl group can be straight-chain or branched. R3 and R4 can also be bonded to each other to form a ring. When the alkyl group constituting R3 or R4 is straight-chain or branched, the number of carbon atoms in one or both of the alkyl groups is preferably 1 or more and 3 or fewer, more preferably 1 or more and 2 or fewer, and even more preferably 1.

[0089] Furthermore, from the viewpoint of effectively reducing the viscosity of the thickening or gelling agent or effectively inhibiting the thickening and gelling of the agent, X is preferably an alkylene group having 1 or more and 5 or less carbon atoms, more preferably an alkylene group having 1 or more and 3 or less carbon atoms, and even more preferably an alkylene group having 1 carbon atom.

[0090] Examples of oximes shown in formula (2) where R3 and R4 represent alkyl groups with 1 or more hydrogen atoms and 5 or fewer carbon atoms include dimethylglyoxime, methylethylglyoxime, diethylglyoxime, 2,4-pentanedione dioxime, etc.

[0091] From the viewpoint of effectively reducing the viscosity of thickening or gelling agents or effectively inhibiting thickening and gelling of agents, oximes are preferably those shown in formula (1) where R1 and R2 independently represent alkyl groups having 1 or more hydrogen atoms and 5 or fewer carbon atoms, or those shown in formula (2) where R3 and R4 independently represent alkyl groups having 1 or more hydrogen atoms and 5 or fewer carbon atoms. Among these, oximes shown in formula (1) where R1 and R2 independently represent alkyl groups having 1 or more hydrogen atoms and 5 or fewer carbon atoms are preferred.

[0092] It should be noted that some or all of the hydrogen atoms of the alkyl group in the oxime shown in formula (1) and the oxime shown in formula (2) may be replaced by alkyl, aryl, hydroxyl or amino groups with 1 or more but less than 10 carbon atoms.

[0093] In the oxime content of the mixture, the amount of hydroxyimino groups in the oxime is preferably 6.0 mmol or more and 80.0 mmol or less relative to 1 g of vinylidene fluoride polymer, more preferably 25.0 mmol or more and 80.0 mmol or less, even more preferably 50.0 mmol or more and 80.0 mmol or less, and particularly preferably 50.0 mmol or more and 75.0 mmol or less. Increasing the amount of hydroxyimino groups effectively reduces the viscosity of the thickening or gelling mixture, or effectively inhibits thickening and gelling of the mixture. On the other hand, by setting the amount of hydroxyimino groups to 80.0 mmol or less relative to 1 g of vinylidene fluoride polymer, it is possible to prevent an extreme decrease in the viscosity of the mixture, which would reduce its coatability and make it impossible to control the thickness of the coating layer.

[0094] Furthermore, regarding the oxime content in the mixture, the amount of hydroxyimino groups present in the oxime is preferably 2.0 mmol or more and 70.0 mmol or less per 1g of solid electrolyte, more preferably 10.0 mmol or more and 70.0 mmol or less, and even more preferably 20.0 mmol or more and 60.0 mmol or less. Increasing the amount of hydroxyimino groups effectively reduces the viscosity of the thickening or gelling mixture, or effectively inhibits thickening and gelling of the mixture. On the other hand, by setting the amount of hydroxyimino groups to 70.0 mmol or less per 1g of solid electrolyte, it is possible to prevent an extreme decrease in the viscosity of the mixture, which would reduce its coatability and make it difficult to control the thickness of the coating layer.

[0095] (Polyvinylidene fluoride polymer)

[0096] Vinylidene fluoride polymers function as binders for bonding solid electrolytes together or for bonding solid electrolytes to positive or negative electrode active materials. Furthermore, vinylidene fluoride polymers also function as binders for bonding them to current collectors.

[0097] Polymers of vinylidene fluoride can be homopolymers of vinylidene fluoride or copolymers of vinylidene fluoride with monomers that can be copolymerized with vinylidene fluoride.

[0098] When the vinylidene fluoride polymer is a copolymer, it can also be a copolymer with any known monomer that can copolymerize with vinylidene fluoride.

[0099] When the vinylidene fluoride polymer is a copolymer, it can be a copolymer with the compound shown in formula (3) below, perfluoroalkyl vinyl ethers, unsaturated diacids, and esters of unsaturated diacids. It should be noted that the vinylidene fluoride polymer that is a copolymer can be a copolymer with one of these compounds or a copolymer with multiple of these compounds.

[0100] [Chemical Formula 3]

[0101]

[0102] In formula (3), R5 represents a hydrogen atom, an alkyl group having 1 or more but 5 or fewer carbon atoms, or a carboxyl group substituted with an alkyl group having 1 or more but 5 or fewer carbon atoms. R6 and R7 independently represent a hydrogen atom or an alkyl group having 1 or more but 5 or fewer carbon atoms. The aforementioned alkyl groups can be linear or branched. From the viewpoint of facilitating the polymerization reaction, R5 and R6 are preferably substituents with low steric hindrance. Specifically, R5 and R6 are independently preferably hydrogen or an alkyl group having 1 or more but 3 or fewer carbon atoms, more preferably hydrogen or methyl.

[0103] In formula (3), Y is a group of atoms with a molecular weight of 500 or less, consisting of a single bond or a main chain composed of 1 to 20 atoms. More preferably, the molecular weight of the aforementioned group is 200 or less. There is no particular limitation on the lower limit of the molecular weight of the aforementioned group, but it is usually 15. The smaller the molecular weight of the aforementioned group, the less likely the mixture will thicken or gel. In this specification, "number of atoms in the main chain" refers to the number of atoms required to combine the carboxyl group on the right side of Y in formula (3) with the group (R5R6C=CR) on the left side of Y. 7- The number of atoms in the backbone of the chain formed by connecting the atoms. It should be noted that Y can be a straight chain or a branched chain containing functional groups as side chains. When it has side chains, Y can have only one side chain or multiple side chains. It should be noted that when Y is a single bond, the compound shown in formula (3) has a structure in which the carboxyl group is directly bonded to the carbon atom bonded to R7.

[0104] Examples of compounds shown in formula (3) include: acrylic acid (AA), methacrylic acid, 2-carboxyethyl acrylate (CEA), 2-carboxyethyl methacrylate, monomethyl maleate, acryloyloxyethyl succinic acid (AES), acryloyloxypropyl succinic acid (APS), methacryloyloxyethyl succinic acid, methacryloyloxypropyl succinic acid, etc. Only one of these compounds may be used, or multiple compounds may be used in combination.

[0105] Examples of perfluoroalkyl vinyl ethers include: vinyl fluoride, trifluoroethylene (TFE), tetrafluoroethylene (TrFE), trifluorochloroethylene (CTFE), hexafluoropropylene (HFP), and perfluoromethyl vinyl ethers.

[0106] Examples of unsaturated dicarboxylic acids include maleic acid, fumaric acid, and citralic acid.

[0107] Examples of esters of unsaturated dicarboxylic acids include monomethyl maleate (MMM), monoethyl maleate, monomethyl citrate, and monoethyl citrate.

[0108] The vinylidene fluoride polymer contains at least 50 mol% of vinylidene fluoride-derived structural units relative to all structural units, preferably at least 80 mol%, and more preferably at least 90 mol%. There is no particular upper limit on the amount of vinylidene fluoride-derived structural units; it can be set to 100 mol%.

[0109] Furthermore, in the vinylidene fluoride polymer, the amount of structural units derived from compounds other than vinylidene fluoride is 50 mol% or less, preferably 20 mol% or less, and more preferably 10 mol% or less, relative to all structural units. There is no particular limitation on the structural units derived from compounds other than vinylidene fluoride, as long as they are more than 0 mol% when it is a copolymer.

[0110] The amount of structural units derived from vinylidene fluoride and the amount of structural units derived from compounds other than vinylidene fluoride can be determined by copolymerization. 1 H NMR spectrum or 19 The result can be determined by F NMR spectroscopy or neutralization titration.

[0111] The vinylidene fluoride polymer can also be a vinylidene fluoride polymer containing less than 0.5 wt% of fluorinated compounds other than vinylidene fluoride. According to the inventors, the viscosity of an additive containing less than 0.5 wt% of a vinylidene fluoride polymer containing fluorinated compounds other than vinylidene fluoride can be effectively reduced by adding an oxime after thickening or gelling.

[0112] Furthermore, the vinylidene fluoride polymer can also be a vinylidene fluoride polymer containing 0.5 wt% or more of fluorinated compounds other than vinylidene fluoride. According to the inventors' understanding, the viscosity of an additive containing 0.5 wt% or more of a vinylidene fluoride polymer containing fluorinated compounds other than vinylidene fluoride can be effectively reduced by adding an oxime after thickening or gelling. Furthermore, the thickening and gelling of an additive containing 0.5 wt% or more of a vinylidene fluoride polymer containing fluorinated compounds other than vinylidene fluoride can be effectively suppressed by adding an oxime during slurry formation when mixing with a non-aqueous solvent.

[0113] It should be noted that examples of fluorinated compounds that may be included in these vinylidene fluoride polymers include the aforementioned perfluoroalkyl vinyl ethers. Among these, hexafluoropropylene (HFP), chlorotrifluoroethylene (CTFE), and trifluoroethylene (TFE) are preferred, especially considering the high thickening and gelation inhibition effects achieved by adding oxime during slurrying. Hexafluoropropylene (HFP) and chlorotrifluoroethylene (CTFE) are more preferred.

[0114] Specific Concentration Logarithmic Viscosity (η) of Polyvinylidene Fluoride iThere are no particular limitations, but it is preferably 0.5 dl / g or more and 5.0 dl / g or less, more preferably 1.0 dl / g or more and 4.5 dl / g or less, and even more preferably 1.5 dl / g or more and 4.0 dl / g or less. When the specific logarithmic viscosity is within the above range, uneven thickness during coating is less likely to occur, and the positive electrode layer, negative electrode layer, and solid electrolyte layer can be fabricated more easily.

[0115] Logarithmic viscosity (η) i The specific viscosity (η) is calculated using the following method: 80 mg of vinylidene fluoride polymer is dissolved in 20 mL of N,N-dimethylformamide to prepare a polymer solution. The viscosity η of the prepared polymer solution is measured using an Ubbelohde viscometer in a constant temperature bath at 30°C. Then, the specific logarithmic viscosity (η) is calculated according to the following formula. i ).

[0116] η i =(1 / C)・ln(η / η0)

[0117] In the above formula, η0 is the viscosity of N,N-dimethylformamide as a solvent, and C is the concentration of vinylidene fluoride polymer in the prepared polymer solution (0.4 g / dL).

[0118] There are no particular limitations on the polymerization method for vinylidene fluoride polymers, and conventionally known polymerization methods can be used. Examples of polymerization methods include suspension polymerization, emulsion polymerization, and solution polymerization. Among these, aqueous suspension polymerization or emulsion polymerization is preferred from the perspective of ease of post-processing, and aqueous suspension polymerization is more preferred.

[0119] The content of the vinylidene fluoride polymer in the compound used to form the electrode layers (positive electrode layer and negative electrode layer) relative to the total amount of solid components can be set to 0.2% by mass or more and 20% by mass or less, preferably 0.2% by mass or more and 10% by mass or less, more preferably 0.2% by mass or more and 4% by mass or less.

[0120] The content of the vinylidene fluoride polymer in the compound used to form the solid electrolyte layer, relative to the total amount of the solid components, can be set to 0.5% by mass or more and 80% by mass or less, preferably 0.5% by mass or more and 50% by mass or less, and more preferably 0.5% by mass or more and 20% by mass or less.

[0121] (Solid electrolyte)

[0122] Examples of solid electrolytes include well-known sulfide-based solid electrolytes and oxide-based solid electrolytes.

[0123] Examples of sulfide-based solid electrolytes include: Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2O-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li2S-P2S5, and Li3PS4, etc.

[0124] Examples of oxide-based solid electrolytes include: LLTO compounds ((La,Li)TiO3), Li6La2CaTa2O 12 Li6La2ANb2O 12 (A: Alkaline earth metal), Li₂Nd₃TeSbO 12 Li3BO 2.5 N 0.5 Li9SiAlO8, LAGP series compounds (Li 1+x Al x Ge 2-x LATP compounds such as (PO4)3 (0≤x≤1) and Li2O-Al2O3-TiO2-P2O5 (Li 1+ x Al x Ti 2-x (PO4)3 (0≤x≤1) , Li 1+x Ti 2-x Al x Si y (PO4) 3-y (0≤x≤1, 0≤y≤1), Li 1+y Al x M 2-x (PO4)3 (M is Ti, Ge, Sr, Sn, Zr or Ca, 0≤x≤1, 0≤y≤1), LiTi x Zr 2-x (PO4)3 (0≤x≤1), LISICON (Li 4- 2x Zn x GeO4 (0≤x≤1) and LIPON compounds (Li 3+y PO 4-x N x (0≤x≤1, 0≤y≤1)), NASICON series compounds (LiTi2(PO4)3, etc.), garnet series compounds (Li7La3Zr2O) 12 Li 7-x La3Zr 1-x Nb x O 12 (0≤x≤1) etc.

[0125] From the perspective of high lithium-ion conductivity, oxide-based solid electrolytes are preferably garnet-based compounds. As garnet-based compounds, materials represented by the following formula (4) are preferred:

[0126] Li 7-x La3 (Zr) 2-x M x )O 12 ... (4)

[0127] (In equation (4), M = Nb or Ta, and x satisfies 0 ≤ x ≤ 2). Examples of materials shown in equation (4) include Li7La3Zr2O. 12 (LLZO), etc.

[0128] It should be noted that the solid electrolyte is preferably a compound whose extraction water has a pH of 10.5 or higher when extracted with water at room temperature (25°C) using the extraction method specified in JIS K 5101-16-2 (2004). Such a solid electrolyte easily defluorinates the vinylidene fluoride polymer, which can easily lead to thickening of the mixture. However, the mixture of this embodiment can suppress the increase in viscosity through oxime.

[0129] Specifically, the pH of the extracted water was obtained as follows: the electrode active material was placed in 50 times its weight of ultrapure water, stirred at 600 rpm for 10 minutes using a magnetic stirrer, and the pH of the extracted water was measured using a pH meter manufactured by Horiba Corporation, model F-21.

[0130] The compound containing the positive electrode active material with a pH of 10.5 or higher from the extraction water described above contains a large amount of alkali, which easily leads to the deterioration of vinylidene fluoride and thus thickening. Therefore, normally, in order to suppress the thickening of the slurry-like compound and the resulting gelation, it is necessary to remove the alkali by washing the positive electrode active material with water. In contrast, the compound of this embodiment is less prone to thickening and gelation even when using such a positive electrode active material containing a large amount of alkali. Therefore, the compound of this embodiment can be manufactured without washing the positive electrode active material with water.

[0131] Furthermore, the volume average particle size of the above-mentioned oxide-based solid electrolyte is not particularly limited, but is preferably 0.01 μm or more and 100 μm or less, preferably 0.05 μm or more and 50 μm or less, and more preferably 0.1 μm or more and 10 μm or less.

[0132] (Electrode active material)

[0133] The above-mentioned mixture may be a mixture containing an electrode active material for forming a positive electrode layer or a negative electrode layer, or may be a mixture containing no electrode active material for forming a solid electrolyte layer.

[0134] The electrode active material intercalates or deintercalates ions such as lithium ions. The electrode active material thereby enables charging and discharging of the secondary battery.

[0135] The electrode active material may be a positive electrode active material or a negative electrode active material.

[0136] The positive electrode active material is not particularly limited, and a lithium metal oxide is preferred.

[0137] Examples of lithium metal oxides include: LiMnO2, LiMn2O4, LiCoO2, LiNiO2, LiNi x Co 1-x O2 (0<x<1), LiNi x Co y Mn 1-x-y O2 (0<x<1, 0<y<1), LiNi x Co y Al 1-x-y O2 (0<x<1, 0<y<1), LiFePO4, and the like.

[0138] From the viewpoint of increasing the capacity density to achieve high capacity of the secondary battery, the positive electrode active material is preferably a lithium metal compound containing Ni. Further, from the viewpoint of suppressing changes in the crystal structure during charging and discharging to stabilize cycle characteristics, the positive electrode active material is more preferably a lithium metal compound containing Ni and Co.

[0139] From the viewpoint of increasing the charging potential of the secondary battery and further improving the cycle characteristics, the positive electrode compound is preferably a lithium metal oxide (ternary lithium metal oxide) represented by the following formula (5).

[0140] LiNi x Co y M z O2……(5)

[0141] In formula (5), M is Mn or Al, 0<x<1, 0<y<1, 0<z<1, and x+y+z=1.

[0142] Examples of the ternary lithium metal oxide include: Li 1.00 Ni 0.5 Co 0.2 Mn 0.3 O2 (NCM532), Li 1.00 Ni 0.6 Co 0.2 Mn0.2 O2 (NCM622), Li 1.00 Ni 0.83 Co 0.12 Mn 0.05 O2 (NCM811) and Li 1.00 Ni 0.85 Co 0.15 Al 0.05 O2 (NCA811), etc.

[0143] There are no particular limitations on the negative electrode active material; known materials such as carbon materials, metal / alloy materials, and metal oxides can be used. Among these, carbon materials are preferred from the viewpoint of further improving the energy density of the secondary battery. Examples of carbon materials include: artificial graphite, natural graphite, difficult-to-graphitize carbon, and easily-graphitize carbon.

[0144] These electrode active materials can be used in single or multiple ways.

[0145] The content of electrode active material in the compound is preferably 40% by mass or more and 99.9% by mass or less relative to the total amount of solid components. When the amount of active material is within this range, sufficient charge and discharge capacity can be obtained, and battery performance tends to be good.

[0146] (Non-aqueous solvent)

[0147] The mixture can be either a slurry containing non-aqueous solvents or a mixture of powders or particles that do not contain non-aqueous solvents.

[0148] Examples of non-aqueous solvents include: N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, hexamethylphosphoramide, dioxane, tetrahydrofuran, tetramethylurea, triethyl phosphate, trimethyl phosphate, acetone, ethyl acetate, n-butyl acetate, n-butanol, dipropylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, cyclohexanone, toluene, diisobutyl ketone, butyl butyrate, and methyl ethyl ketone. Among these, diisobutyl ketone is preferred when using a sulfide-based solid electrolyte, and N-methyl-2-pyrrolidone is preferred when using an oxide-based solid electrolyte. Only one of these non-aqueous solvents may be used, or multiple solvents may be used in combination.

[0149] There is no particular limitation on the amount of solid components in the mixture, but it is preferably 10 parts by mass or more and 85 parts by mass or less relative to the total amount of components in the slurry.

[0150] (Other substances)

[0151] The mixture may also contain polymers other than vinylidene fluoride polymers, conductive additives, pigment dispersants, insulating fillers, lithium salts, dispersing stabilizers, adhesive aids, thickeners, dispersants, flame retardants, defoamers, and various coupling agents, etc.

[0152] Examples of conductive additives include carbonaceous materials such as carbon black, carbon nanotubes, graphite powder and graphite fiber, as well as metal powders and fibers such as nickel and aluminum.

[0153] Examples of pigment dispersants include polyvinylpyrrolidone, etc.

[0154] Examples of insulating fillers include: insulating inorganic fillers such as alumina, magnesium oxide, and silicon dioxide, and insulating organic fillers such as polytetrafluoroethylene, polyimide, and polyacrylonitrile.

[0155] Examples of plasticizers include ethylene carbonate, propylene carbonate, and methyl ethyl carbonate.

[0156] Examples of lithium salts include LiPF6, LiFSI, and LiTFSI.

[0157] The content of these other substances in the mixture is preferably less than 15% by mass relative to the total amount of solid components.

[0158] [Preparation method of the compound]

[0159] The mixture can be made by mixing the above-mentioned ingredients.

[0160] There are no particular limitations on the mixing method. The oxime, vinylidene fluoride polymer, and solid electrolyte can be dry-mixed, or they can be wet-mixed together with a non-aqueous solvent. The mixture obtained through dry mixing simply needs to be mixed with a non-aqueous solvent to form a slurry during battery manufacturing.

[0161] Furthermore, the mixture containing a non-aqueous solvent can be mixed with the oxime during preparation, or the oxime can be added after thickening or gelling the slurry (composition) obtained by wet mixing of the vinylidene fluoride polymer and the solid electrolyte with a non-aqueous solvent. Alternatively, the oxime can be added during preparation while the vinylidene fluoride co-weight and the oxime are pre-dissolved in a non-aqueous solvent. Similarly, the oxime can be added during preparation while dissolved in a non-aqueous solvent in which the solid electrolyte is pre-dispersed, or while dissolved in a non-aqueous solvent in which the electrode active material is pre-dispersed.

[0162] According to the inventors' understanding, if an oxime is added after thickening or gelling a slurry-like composition comprising a solid electrolyte, a vinylidene fluoride polymer, and a non-aqueous solvent, the viscosity of the composition can be reduced, making it easier to coat (first manufacturing method: viscosity preparation method of the mixture). Furthermore, depending on the type of vinylidene fluoride polymer, by mixing the oxime together when preparing the slurry by mixing the solid electrolyte, the vinylidene fluoride polymer, and the non-aqueous solvent, thickening and gelation of the slurry-like mixture can be suppressed (second manufacturing method).

[0163] (First manufacturing method)

[0164] In the first manufacturing method, a composition comprising a vinylidene fluoride polymer, a solid electrolyte, and a non-aqueous solvent is prepared, and an oxime is added to the composition.

[0165] The composition can be prepared using well-known methods, such as simply stirring and mixing the vinylidene fluoride polymer, solid electrolyte, and non-aqueous solvent. There are no particular limitations on the method of adding the components during mixing. The vinylidene fluoride polymer, solid electrolyte, and non-aqueous solvent can be added separately to the mixing container and mixed simultaneously, or several of these components can be premixed, and the resulting premix can be mixed with the remaining components. Furthermore, the components can be added all at once or in stages. By mixing these components, a slurry-like composition can be obtained.

[0166] It should be noted that when fabricating the positive or negative electrode layer, the positive or negative active material is mixed in during the composition preparation. When fabricating the solid electrolyte layer, the positive or negative active material is not mixed in during the composition preparation. Furthermore, if the composition contains other additives, these additives are mixed in during the composition preparation.

[0167] The oxime is added after the preparation of the above composition. The above composition is prone to thickening and gelling after preparation. By adding oxime to the thickening or gelling composition, the viscosity of the composition can be reduced or its fluidity restored, adjusting the viscosity of the mixture to a coatable range. When adding oxime to a gelling composition, the composition can be pulverized beforehand to facilitate oxime penetration. Alternatively, the viscosity of the composition can be reduced by allowing the oxime to penetrate after adding it and letting it stand for a certain period of time, or by adding and stirring the oxime and then allowing it to penetrate for a certain period of time.

[0168] According to the inventors' understanding, in the first manufacturing method, regardless of the type of vinylidene fluoride polymer, the viscosity of the composition can be reduced or the fluidity restored by adding oxime.

[0169] (Second manufacturing method)

[0170] In the second manufacturing method, oxime, vinylidene fluoride polymer, solid electrolyte and non-aqueous solvent are prepared and mixed to make a slurry-like mixture.

[0171] Mixing can be carried out using any known method. There are no particular limitations on the method of adding the components during mixing. The oxime, vinylidene fluoride polymer, solid electrolyte, and non-aqueous solvent can be added separately to the mixing container and mixed simultaneously, or several of these components can be premixed, and the resulting premix can be mixed with the remaining components. Furthermore, the components can be added all at once or in stages. By mixing these components, a slurry-like mixture can be obtained.

[0172] It should be noted that when fabricating the positive or negative electrode layer, the positive or negative active material is mixed in during the preparation of the compound. When fabricating the solid electrolyte layer, it is unclear whether the positive or negative active material is not mixed in during the preparation of the compound. Furthermore, if the compound contains other additives, these additives are also mixed in.

[0173] The thickening and gelation of the resulting mixture are thus suppressed. Furthermore, the viscosity may sometimes decrease over time after preparation.

[0174] For example, in the slurry-like mixture manufactured by the second manufacturing method, the ratio (η2 / η1) of the slurry viscosity (η2) after 3 hours from preparation to the slurry viscosity (η1) immediately after preparation is 1.00 or less, preferably 0.95 or less, and more preferably 0.90 or less.

[0175] According to the inventors' understanding, in the second manufacturing method, when preparing an additive containing a fluorinated compound other than vinylidene fluoride in an amount of 0.5 wt% or more, thickening and gelation of the additive can be significantly suppressed, and the viscosity can be reduced after preparation.

[0176] It should be noted that in the manufacture of the mixture using the first and second manufacturing methods, kits containing the mixture materials in multiple containers can also be used. These kits can be configured to include containers containing vinylidene fluoride polymers and containers containing oximes, containers containing solid electrolytes and containers containing oximes, containers containing electrode active materials and containers containing oximes, etc. The mixture can be manufactured using the materials contained in these kits and other materials, and by employing the first or second manufacturing method described above.

[0177] At this point, the oxime included in the kit can be selected for use in either the first or second manufacturing method, depending on the type of vinylidene fluoride polymer. That is, the aforementioned oxime can be used after thickening or gelling the prepared composition, regardless of the type of vinylidene fluoride polymer (first manufacturing method). Alternatively, the oxime can be added during the preparation of a mixture containing a vinylidene fluoride polymer suitable for the second manufacturing method (e.g., a vinylidene fluoride polymer containing 0.5 wt% or more of fluorinated compounds other than vinylidene fluoride) (second manufacturing method).

[0178] [Battery components and their manufacturing methods]

[0179] The above-mentioned compound can be used in the manufacture of battery components, specifically in the manufacture of the positive electrode layer, negative electrode layer, and solid electrolyte layer.

[0180] Specifically, these layers can be made by applying the above-mentioned mixture onto a substrate and allowing it to dry.

[0181] The substrate can be a transfer sheet, a transfer substrate, or other pre-formed layers. It can also be a current collector when fabricating the positive or negative electrode layer. When coating the transfer sheet or transfer substrate with an adhesive and allowing it to dry, layers formed on these substrates can be transferred to the pre-formed layers. By stacking the layers of the secondary battery in the order of positive electrode layer, solid electrolyte layer, negative electrode layer, solid electrolyte layer, positive electrode layer, etc., and connecting the current collector to the positive and negative electrode layers as needed, a secondary battery can be obtained.

[0182] Coating and drying can be performed using known methods. For example, coating can be performed using a doctor blade, reverse roller, comma bar, gravure, air knife, die coating, and dip coating. The drying temperature can be set to 20°C or higher and 250°C or lower, preferably 40°C or higher and 200°C or lower, more preferably 60°C or higher and 180°C or lower. The drying time can be set to 10 seconds or higher and 300 minutes or lower, preferably 1 minute or higher and 200 minutes or lower. It should be noted that drying can be performed multiple times at different temperatures. Pressure can also be applied during drying.

[0183] The resulting components (positive electrode layer, negative electrode layer, or solid electrolyte layer) have a mixture layer containing a vinylidene fluoride polymer and a solid electrolyte, and may contain electrode active materials and other additives as needed. Drying allows for complete volatilization of the oxime, although some may remain in the mixture layer. The residual amount of oxime is not particularly limited and can be set to greater than 0 μg / m³. 2 (Or above the detection limit) and 500 μg / m 2 the following.

[0184] These components can be used in all-solid-state batteries and semi-solid-state batteries.

[0185] [Other Implementation Methods]

[0186] It should be noted that the above-described embodiments are exemplary embodiments of the present invention, and the present invention can of course include embodiments other than those described above within the scope of its core technical ideas.

[0187] Example

[0188] The present invention will be described in detail based on the embodiments, but the present invention is not limited to these embodiments.

[0189] 1. Preparation of vinylidene fluoride polymer

[0190] 1-1. Preparation of VDF homopolymer (Preparation Example 1)

[0191] 1026g of deionized water, 0.2g of methylcellulose, 400g of vinylidene fluoride monomer, 2.4g of di-n-propyl peroxide, 2.4g of methanol, and 3.0g of ethyl acetate were added to a 2-liter autoclave. The polymerization temperature was set to 26℃, and then increased to 40℃ for 12 hours for suspension polymerization. After polymerization, the resulting polymer slurry was heat-treated at 95℃ for 30 minutes, followed by dehydration, washing, and further drying at 80℃ for 20 hours to obtain VDF homopolymer.

[0192] 1-2. Preparation of VDF / HFP copolymers (Preparation Example 2)

[0193] 1160g of deionized water, 0.6g of methylcellulose, 360g of vinylidene fluoride (VDF), 40g of hexafluoropropylene (HFP), and 3.6g of diisopropyl peroxide dicarbonate were charged into a 2-liter autoclave, and polymerization was carried out at 45°C. The resulting copolymer was heat-treated at 95°C for 60 minutes, followed by dehydration, washing, and drying at 80°C for 20 hours to obtain the VDF / HFP copolymer.

[0194] 1-3. Preparation of VDF / HFP / MMM copolymer (Preparation Example 3)

[0195] 1160g of deionized water, 0.6g of methylcellulose, 344g of vinylidene fluoride (VDF), 56g of hexafluoropropylene (HFP), 2.2g of monomethyl ethyl maleate (MMM), and 3.6g of diisopropyl peroxide dicarbonate were charged into a 2-liter autoclave, and polymerization was carried out at 45°C. The resulting copolymer was heat-treated at 95°C for 60 minutes, followed by dehydration, washing, and drying at 80°C for 20 hours to obtain the VDF / HFP / MMM copolymer.

[0196] 1-4. Preparation of VDF / APS copolymer (Preparation Example 4)

[0197] 1096 g of deionized water, 0.2 g of METOLOSE 90SH-100 (manufactured by Shin-Etsu Chemical Co., Ltd.), 2.2 g of 50 wt% diisopropyl peroxide-CFC 225cb solution, 426 g of vinylidene fluoride, and an initial addition of 0.2 g of acryloyloxypropyl succinic acid (APS) were added to a 2-liter autoclave. After heating to 26°C over 1 hour, the temperature was maintained at 26°C, and a 6 wt% APS aqueous solution was slowly added at a rate of 0.5 g / min. The resulting polymer slurry was dehydrated and dried to obtain the VDF / APS copolymer. The total amount of APS added, including the initial addition, was 4.0 g.

[0198] 1-5. Preparation of VDF / TFE copolymer (Preparation Example 5)

[0199] 1300g of deionized water was added to a 4L autoclave, and after thorough nitrogen purging, 1300g of octafluorocyclobutane was added. The system was maintained at 37°C and a stirring speed of 580rpm. Then, 200g of a mixed gas containing trifluoroethylene (TFE) and vinylidene fluoride (VDF) in a TFE / VDF ratio of 9 / 91 by mass, 0.4g of ethyl acetate, and 1g of a 50% by mass methanol solution of di-n-propyl peroxide were added to initiate polymerization. As the pressure in the system decreased during polymerization, a mixed gas with a TFE / VDF ratio of 28 / 72 by mass was continuously supplied to maintain the pressure at 1.3MPaG. Stirring was continued for 17 hours to obtain the VDF / TFE copolymer.

[0200] 1-6. Preparation of VDF / AA copolymer (Preparation Example 6)

[0201] 524 g of deionized water, 0.4 g of METOLOSE 90SH-100 (manufactured by Shin-Etsu Chemical Co., Ltd.), 4 g of 50 wt% tert-butyl peroxypentanoate-CFC 225cb solution, 396 g of vinylidene fluoride, and an initial addition of 0.2 g of acrylic acid (AA) were added to a 2-liter autoclave, and the mixture was heated to 50°C. Under constant pressure during polymerization, a 1 wt% aqueous solution of AA was continuously supplied to the reaction vessel. The resulting polymer slurry was dehydrated and dried to obtain the VDF / AA copolymer. The total amount of AA added, including the initial addition, was 3.96 g.

[0202] 1-7. Preparation of VDF / CTFE copolymer (Preparation Example 7)

[0203] 1040g of deionized water, 0.2g of methylcellulose, 384g of vinylidene fluoride (VDF), 16g of chlorotrifluoroethylene (CTFE), and 2.0g of diisopropyl peroxide dicarbonate were charged into a 2-liter autoclave, and polymerization was carried out at 45°C. The resulting copolymer was heat-treated at 95°C for 60 minutes, followed by dehydration, washing, and drying at 80°C for 20 hours to obtain the VDF / CTFE copolymer.

[0204] 1-8. Preparation of VDF / HFP / AA copolymer (Preparation Example 8)

[0205] 1316 g of deionized water, 0.4 g of METOLOSE SM-100 (manufactured by Shin-Etsu Chemical Co., Ltd.), 2.4 g of diisopropyl peroxide, 400 g of vinylidene fluoride (VDF), 4 g of hexafluoropropylene (HFP), and an initial addition of 0.2 g of acrylic acid (AA) were added to a 2-liter autoclave, and the mixture was heated to 50°C. Under constant pressure during polymerization, a 1% by weight aqueous solution of AA was continuously supplied to the reaction vessel. The resulting polymer slurry was dehydrated and dried to obtain the VDF / HFP / AA copolymer. The total amount of AA added, including the initial addition, was 4 g.

[0206] 1-9. Determination of Polymerization Ratio

[0207] Determine the composition of each polymer powder according to the following conditions. 1 1H NMR spectroscopy. An AVANCE AC 400FT NMR spectrometer (manufactured by Bruker) was used as the instrument.

[0208] <Measurement Conditions>

[0209] Frequency: 400MHz

[0210] Solvent for determination: DMSO-d6

[0211] Measurement temperature: 25℃

[0212] according to 1 The amount of structural units derived from vinylidene fluoride and the amount derived from comonomers in the polymer were calculated using 1H NMR spectroscopy. Specifically, the calculations were based on the integrated intensities of the signals primarily derived from comonomers and primarily derived from vinylidene fluoride observed at 2.24 ppm and 2.87 ppm, respectively.

[0213] When using comonomers having structures derived from acrylic acid or monomethyl maleate as comonomers, the amount of structural units containing structures derived from acrylic acid or monomethyl maleate in the polymer was determined by neutralization titration using a 0.03 mol / L aqueous sodium hydroxide solution. More specifically, the titrant was prepared by dissolving 0.3 g of the polymer in 9.7 g of acetone at approximately 80 °C, followed by the addition of 3 g of pure water. Neutralization titration was performed at room temperature using phenolphthalein as an indicator and a 0.03 mol / L aqueous sodium hydroxide solution.

[0214] 2. Preparation of the mixture (first manufacturing method)

[0215] The VDF homopolymer obtained in Preparation Example 1 was dissolved in N-methyl-2-pyrrolidone (NMP) to prepare a 10 wt% binder solution. LLZO (solid electrolyte) and the binder solution were weighed and mixed.

[0216] The mass ratio of solid electrolyte to VDF homopolymer in compound 1 (solid electrolyte:VDF homopolymer) is 10:90.

[0217] After preparation, the viscosity of the mixture was measured after standing for 2 days. Then, 2-Butanone oxime was added to the mixture, and it was stirred at 2000 rpm for 3 minutes using a Rentarō stirrer (manufactured by THINKY Corporation). At this time, the amount added was adjusted so that 1g of vinylidene fluoride polymer contained 57.4 mmol of 2-Butanone oxime (0.06 mol of hydroxyimino). Then, after adding the oxime and stirring, the viscosity of the mixture was measured after 3 hours.

[0218] Mixtures 2 to 8 were prepared by changing the type of VDF polymer, the type of oxime, and their respective mass ratios. Similarly, the viscosity was measured after standing, before adding oxime, after adding and stirring oxime, and after adding oxime.

[0219] Using an E-type viscometer, at 25°C and a shear rate of 2s... -1 The viscosity is measured. Specifically, the slurry (mixture) is loaded into the measuring device and left to stand for 60 seconds, then the rotor is rotated to measure the viscosity. The value taken 300 seconds after the rotor begins rotating is then recorded as the slurry viscosity.

[0220] Table 1 shows the types of VDF polymers used to prepare mixtures 1 through 8, the types and amounts of oximes added, the slurry composition (mass ratio of solid electrolyte, vinylidene fluoride polymer, and added oxime), and the viscosities of the mixtures before and after the addition of oximes. It should be noted that the amount of oxime added represents the amount of hydroxyimino relative to 1g of VDF polymer ("Amount Added A" in the table) or the amount of hydroxyimino relative to 1g of solid electrolyte ("Amount Added B" in the table). Furthermore, when viscosity cannot be measured due to gelation, it is indicated as "gelation".

[0221] [Table 1]

[0222]

[0223] 3. Preparation of the mixture (Second manufacturing method)

[0224] The VDF / HFP copolymer obtained in Preparation Example 2 was dissolved in N-methyl-2-pyrrolidone (NMP) to prepare a 10 wt% adhesive solution.

[0225] LLZO (solid electrolyte), binder solution, and 2-butanone oxime were mixed to prepare compound 9. The mass ratio of the solid electrolyte to the VDF / HFP copolymer in compound 9 (solid electrolyte:VDF / HFP copolymer) was 20:80. Furthermore, at this time, the amount of hydroxyimino group of 2-butanone oxime relative to 1 g of vinylidene fluoride polymer was 57.4 mmol.

[0226] By changing the type of VDF polymer, the type of oxime, and their respective mass ratios, mixtures 10 to 22 were prepared. It should be noted that mixtures 19 to 22 did not contain any oxime.

[0227] Using an E-type viscometer, at 25°C and a shear rate of 2s... -1 Viscosity was measured. Specifically, the slurry (mixture) was loaded into the measuring device and left to stand for 60 seconds, then the rotor was rotated to measure the viscosity. The value 300 seconds after the rotor began rotating was taken as the slurry viscosity. For each mixture prepared, the viscosity was measured immediately after preparation and after storage at 25°C under a nitrogen atmosphere for 3 hours.

[0228] Tables 2 and 3 show the types of VDF polymers used to prepare mixtures 1 through 8, the types of oximes, the slurry composition (mass ratio of solid electrolyte, vinylidene fluoride polymer, and added oxime), and the viscosities of the mixtures immediately after preparation and after 3 hours of storage. It should be noted that the amount of oxime added represents the amount of hydroxyimino relative to 1g of VDF polymer (“Amount Added A” in the table) or the amount of hydroxyimino relative to 1g of solid electrolyte (“Amount Added B” in the table). Furthermore, when viscosity cannot be measured due to gelation, it is indicated as “gelation”.

[0229] [Table 2]

[0230]

[0231] [Table 3]

[0232]

[0233] As shown in Tables 1 to 3, battery additives containing oxime, vinylidene fluoride polymers, and solid electrolytes can reduce viscosity or restore fluidity even when gelled and thickened, and are not prone to gelling and thickening.

[0234] 4. Preparation method of the compound (Third manufacturing method)

[0235] The VDF / HFP copolymer obtained in Preparation Example 2 was dissolved in N-methyl-2-pyrrolidone (NMP) to prepare a 10 wt% adhesive solution.

[0236] LiFePO4 (active material), LLZO (solid electrolyte), Super-P (conductive additive), binder solution, and 2-butanone oxime were mixed to prepare compound 23. The mass ratio of the active material, solid electrolyte, conductive additive, and VDF / HFP copolymer in compound 23 (active material: solid electrolyte: conductive additive: VDF / HFP copolymer) was 80:10:2:10. Furthermore, at this time, the amount of hydroxyimino group in 2-butanone oxime relative to 1 g of vinylidene fluoride polymer was 57.4 mmol.

[0237] By changing the mass ratio of the active substance, solid electrolyte, and oxime, compound 24 and compound 25 were prepared.

[0238] Using an E-type viscometer, at 25°C and a shear rate of 2s... -1 Viscosity was measured. Specifically, the electrode slurry (mixture) was loaded into the measuring device and left idle for 60 seconds, then the rotor was rotated to measure the viscosity. The value 300 seconds after the rotor began rotating was taken as the slurry viscosity. For each mixture prepared, the viscosity was measured immediately after preparation and after storage at 25°C under a nitrogen atmosphere for 3 hours.

[0239] Table 4 shows the types of VDF polymers used to prepare mixtures 23 to 25, the types of oximes, the slurry composition (mass ratio of solid electrolyte, vinylidene fluoride polymer, and added oxime), and the viscosity of the mixtures immediately after preparation and after 3 hours of storage. It should be noted that the amount of oxime added represents the amount of hydroxyimino relative to 1g of VDF polymer (“Amount Added A” in the table) or the amount of hydroxyimino relative to 1g of solid electrolyte (“Amount Added B” in the table). Furthermore, when viscosity cannot be measured due to gelation, it is indicated as “gelation”.

[0240] [Table 4]

[0241]

[0242] As shown in Table 4, the gelation inhibition effect achieved by oxime was also confirmed in battery compounds for electrodes containing active materials.

[0243] This application claims priority to Japanese Patent Application No. 2024-053653, filed March 28, 2024. The matters set forth in the original description and claims of that application are incorporated herein by reference.

[0244] Industrial availability

[0245] This invention can suppress gelation or reduce viscosity of the compound used in the manufacture of solid-state batteries. Therefore, this invention makes the manufacture of solid-state batteries easier.

Claims

1. A battery compound comprising: Oxime; Polyethylene fluoride polymers; and Solid electrolyte.

2. The battery compound according to claim 1, wherein, The ratio (η2 / η1) of the slurry viscosity (η2) after 3 hours from preparation to the slurry viscosity (η1) immediately after slurrying with the addition of non-aqueous solvents is less than 1.

00.

3. The battery compound according to claim 1, wherein, The oxime content is as follows: the amount of hydroxyimino groups in the oxime is 6.0 mmol / g or more and 80.0 mmol / g or less relative to 1g of the vinylidene fluoride polymer.

4. The battery compound according to claim 1, wherein, The oxime content is such that the amount of hydroxyimino groups in the oxime is more than 2.0 mmol / g and less than 70.0 mmol / g relative to the solid electrolyte.

5. The battery compound according to claim 1, wherein, The vinylidene fluoride polymer contains more than 80 mol% of vinylidene fluoride-derived structural units relative to all structural units.

6. A method for adjusting the viscosity of a battery compound, comprising the following steps: The process of preparing a composition comprising a vinylidene fluoride polymer, a solid electrolyte, and a non-aqueous solvent; and The step of adding oxime to the composition.

7. The viscosity adjustment method for the battery compound according to claim 6, wherein, The oxime is added to the gelled composition.

8. A method for manufacturing a battery compound, comprising the following steps: The process of preparing oximes, vinylidene fluoride polymers, solid electrolytes, and non-aqueous solvents; and The process of mixing the oxime, the vinylidene fluoride polymer, the solid electrolyte, and the non-aqueous solvent.

9. The method for manufacturing the battery compound according to claim 8, wherein, The vinylidene fluoride polymer contains 0.5 wt% or more of fluorinated compounds other than vinylidene fluoride.

10. A method for manufacturing a battery component, comprising the following steps: The process of coating and drying the battery compound containing a non-aqueous solvent according to any one of claims 1 to 5.

11. The method for manufacturing a battery component according to claim 10, wherein, The battery compound contains electrode active materials.

12. The method for manufacturing a battery component according to claim 10, wherein, The battery compound does not contain electrode active materials.

13. A battery component manufactured by the method according to claim 10.

14. A secondary battery comprising the battery component according to claim 13.

15. A battery component comprising: Oxime; Polyethylene fluoride polymers; and Solid electrolyte.

16. The battery component according to claim 15, wherein, The battery component contains electrode active materials.

17. The battery component according to claim 15, wherein, The battery component does not contain electrode active materials.

18. A secondary battery comprising a battery component according to any one of claims 15 to 17.

19. A kit for manufacturing a battery compound according to any one of claims 1 to 5. Oxime and other materials are stored in separate containers.

Citation Information

Patent Citations

  • Cutting device

    JP2024053653A

  • Solid-secondary-battery slurry, method for forming solid-secondary-battery layer, and solid secondary battery

    WO2021125150A1

  • Solid secondary battery binding agent, solid secondary battery slurry, method for forming solid secondary battery layer, and solid secondary battery

    WO2022054540A1